Silent suffering: a late presentation of obstetric fistula - D., Gowsika; Palaniappan, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Rectovaginal fistulas are uncommon and account for less than 5% of all anorectal fistulas. Obstetric causes include perineal laceration, episiotomy, assisted vaginal delivery, prolonged labour, and trauma to the genital tract. They usually present with fecal incontinence immediately or within 7-10 days. Other causes include inflammatory bowel disease, diverticulitis, gynaecological surgeries, malignancy, and post-irradiation changes.